LiBerackie doświadczenie estetyczne – na przykładzie twórczości Radosława Nowakowskiego - Błaszczak, Monika (Przestrzenie Teorii, 2024)
On April 4, the opening of the exhibition Always in between beyond over – Radosław Nowakowski’s books took place at the Jagiellonian Library in Krakow. It is worth, in the context of performative and sensual phrases, presenting the achievements of the author of the Cartographic treatise or Sienkiewicz Street in Kielce, especially since the author had the opportunity to participate in this exhibition and interview the creator himself. Liberature – its creation and reading – is an unusual aesthetic experience. In his text-manifesto from 2000, Nowakowski emphasizes “my books are what I want them to be (it is a completely different matter whether books are interested in what I want) – and I want the book to be an integral work, so that all its the elements fit together, had semantic value and took a greater or lesser part in telling this or that story” [source: liberatorium.com]. In his case, the term “total literaturę” takes on an additional meaning: he writes, draws and publishes his books himself. A book becomes a literary work of art – it can be read, looked at, touched, sometimes smelled, tasted or listened to at the same time. The polysensory aesthetic experience becomes both a form of creative, receptive and cognitive practice.